A Systematic Review of Behavioral Interventions to Decrease Opioid Prescribing After Surgery. Issue 2 (February 2020) - Zhang, David D. Q.; Sussman, Jess; Dossa, Fahima; Jivraj, Naheed; Ladha, Karim; Brar, Sav; Urbach, David; Tricco, Andrea C.; Wijeysundera, Duminda N.; Clarke, Hance A.; Baxter, Nancy N.
Abstract : Objective: The aim of this study was to summarize strategies to reduce postsurgical opioid prescribing at discharge. Summary Background Data: Current practices for the prescription of opioids at discharge after surgery are highly variable and often excessive. We conducted a systematic review to identify behavioral interventions designed to improve these practices. Methods: We searched MEDLINE, EMBASE, CINAHL, and PsycINFO until December 14, 2018 to identify studies of behavioral interventions designed to decrease opioid prescribing at discharge among adults undergoing surgery. Behavioral interventions were defined according to the Cochrane Effective Practice and Organisation of Care (EPOC) taxonomy. We assessed the risk of bias of included studies using criteria suggested by Cochrane EPOC and the Newcastle-Ottawa scale. Results: Of 8048 citations that were screened, 24 studies were included in our review. Six types of behavioral interventions were identified: local consensus-based processes (18 studies), patient-mediated interventions (2 studies), clinical practice guidelines (1 study), educational meetings (1 study), interprofessional education (1 study), and clinician reminder (1 study). All but one study reported a statistically significant decrease in the amount of opioid prescribed at discharge after surgery, and only 2 studies reported evidence of increased pain intensity. Reductions in prescribed opioids ranged from 34.4 to 212.3 mg morphine equivalents. All studies were found to have medium-to-high risks of bias. Conclusions: We identified 6 types of behavioral strategies to decrease opioid prescription at discharge after surgery. Despite the risk of bias, almost all types of intervention seemed effective in reducing opioid prescriptions at discharge after surgery without negatively impacting pain control. Abstract : Supplemental Digital Content is available in the text